Ant Colony Optimization: Applications And Trends - Robles Algarín, Carlos Arturo (Ingeniería Solidaria, 2011)
Ants communicate through their pheromones; this is a substance that enables them to find the shortest path between their nest and food source. This feature has been used to solve optimization problems thatneed to improve computation times substantially to solve a specific application. The ant colony optimization (aco) is a meta-heuristic method based on the real behavior of ants. It consists of algorithms used to obtainsolutions to complex problems in a reasonable amount of computing time. The article presents a detailed description of the theory of ant colony optimization, afterwards, it performs a review of the algorithmsused in the aco and finally it shows various applications currently used to demonstrate the benefits ofaco in optimization algorithms. Likewise, it describes new theoretical developments and current trends in thisresearch field.
Keywords: colony; ants; optimization